"We're a Little Biased": Medicine and the Management of Bias through the Case of Contraception. (June 2021) - Manzer, Jamie L.; Bell, Ann V.
There is a wealth of literature demonstrating the presence of bias throughout the American health care system. Despite acknowledging such presence, however, little is known about how bias functions within medical encounters, particularly how providers grapple with bias in their patient counseling and decision-making. We explore such processes through the case of contraceptive counseling, a highly raced, classed, and gendered context. In-depth interviews with 51 health care providers reveal that providers use four primary strategies to navigate and minimize bias in their care—using scientific rationale, employing "safe" biases, standardizing counseling, and implementing patient-centered care. Paradoxically, using these strategies can exacerbate rather than resolve bias. Understanding these bias management strategies reveals provider-held biases, how they manifest within appointments, and the potential consequences for patients' health autonomy. Such knowledge informs interventions that promote contraceptive use among women in the United States, addresses bias in health care broadly, and thus ultimately helps combat health disparities.